2006
DOI: 10.1210/en.2006-0487
|View full text |Cite
|
Sign up to set email alerts
|

The Prolactin-Deficient Mouse Has an Unaltered Metabolic Phenotype

Abstract: Prolactin (PRL), best recognized for its lactogenic activity, is also involved in the regulation of metabolic homeostasis in both mammalian and nonmammalian species. Although several mouse models have been used to study the metabolic functions of PRL, a clear-cut consensus has not emerged given the limited and often conflicting data. To clarify the role of PRL in metabolic homeostasis in males and nonlactating females, we used the PRL-deficient mouse. Our objectives were to compare: 1) weight gain, 2) body com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
51
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 51 publications
4
51
1
Order By: Relevance
“…Such discrepancies may be due to different incubation conditions or species variability. Indeed, we reported that PRL at low concentrations had anti-lipolytic actions on both human and rat adipose explants, but did not affect lipolysis in mouse adipose explants [25].…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Such discrepancies may be due to different incubation conditions or species variability. Indeed, we reported that PRL at low concentrations had anti-lipolytic actions on both human and rat adipose explants, but did not affect lipolysis in mouse adipose explants [25].…”
Section: Discussionmentioning
confidence: 83%
“…Data on PRL and adiponectin are also inconsistent. Whereas serum adiponectin levels are unchanged in PRLR- [6] or PRL-knockout mice [25], PRL at very high doses inhibits adiponectin production in cultured human adipose tissue and in mice in vivo [6,31]. Lower circulating adiponectin levels were reported in lactating women, with inhibition of adiponectin production in cultured human adipocytes by PRL [32].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Accumulating evidence also suggests that PRL is implicated in adipogenesis. Freemark et al reported that PRLR knockout mice have reduced fat deposition, but no such change in adipose mass was detected by a subsequent study (44,45). Given that in vivo adipogenesis is affected by numerous factors, including genetic background, hormone status, age, and the type of food intake, it is reasonable to find that the relationship between PRL and adiposity in intact animals is not conclusive.…”
Section: Discussionmentioning
confidence: 98%
“…Prolactin-receptor mediated signaling is not likely involved in regulating insulin sensitivity in adult mice as both hypoprolactinemic Ames mice and hyperprolactinemic GHR/BP KO mice exhibit enhanced responses to insulin (reviewed in Bartke 2005). In agreement, a recent report utilizing prolactin deficient animals indicates that a lack of prolactin has negligible metabolic effects in mice (LaPensee et al, 2006).…”
Section: Prolactinmentioning
confidence: 89%